PENGARUH CORPORATE GOVERNANCE, AUDITOR EKSTERNAL, DAN UKURAN PERUSAHAAN TERHADAP INTEGRITAS LAPORAN KEUANGAN - Nuraini, 10.05.52.0143; Himmawan Dwi Nugroho, Arief (Students Journal of Accounting and Banking, 2015)
Intention of this research is to analyse corporate governance influence, external auditor, and firm size to the integrity of the financial statements. Integrity of financial statement is how far the financial statement presented show downright and real correct information. Samples are 33 industry of banking on the Stock Exchange of samples (n) = 145. The results showed that there was significant effect between audit committee and external auditor for the integrity of the financial statements, while institutional ownership and independent directors is no significant influence, and there is a significant negative effect between the firm size on the integrity of financial statements.Keywords: Institutional Ownership, Independent Commissioner, Audit Committee, External Auditors, Firm Size, and The Integrity of The Financial Statements